Comparison of laser guidance and freehand hook-wire for CT-guided preoperative localization of pulmonary nodules - Li, Zijian; Zhou, Ziyue; Feng, Kunpeng; Song, Xinyu; Xu, Chun; Li, Chang; Zhao, Jun; Ye, Li; Shen, Ziqing; Ding, Cheng (Journal of cardiothoracic surgery, 2024)
Purpose In VATS surgery, precise preoperative localization is particularly crucial when dealing with small-diameter pulmonary nodules located deep within the lung parenchyma. The purpose of this study was to compare the efficacy and safety of laser guidance and freehand hook-wire for CT-guided preoperative localization of pulmonary nodules. Methods This retrospective study was conducted on 164 patients who received either laser guidance or freehand hook-wire localization prior to Uni-port VATS from September 1st, 2022 to September 30th, 2023 at The First Affiliated Hospital of Soochow University. Patients were divided into laser guidance group and freehand group based on which technology was used. Preoperative localization data from all patients were compiled. The localization success and complication rates associated with the two groups were compared. The risk factors for common complications were analyzed. Results The average time of the localization duration in the laser guidance group was shorter than the freehand group ( p <0.001), and the average CT scan times in the laser guidance group was less than that in the freehand group ( p <0.001). The hook-wire was closer to the nodule in the laser guidance group ( p <0.001). After the localization of pulmonary nodules, a CT scan showed 14 cases of minor pneumothorax (22.58%) in the laser guidance group and 21 cases (20.59%) in the freehand group, indicating no statistical difference between the two groups ( p =0.763). CT scans in the laser guidance group showed pulmonary minor hemorrhage in 8 cases (12.90%) and 6 cases (5.88%) in the freehand group, indicating no statistically significant difference between the two groups ( p =0.119). Three patients (4.84%) in the laser guidance group and six patients (5.88%) in the freehand group had hook-wire dislodgement, showing no statistical difference between the two groups ( p =0.776). Conclusion The laser guidance localization method possessed a greater precision and less localization duration and CT scan times compared to the freehand method. However, laser guidance group and freehand group do not differ in the appearance of complications such as pulmonary hemorrhage, pneumothorax and hook-wire dislodgement.